2016
DOI: 10.3389/fnins.2016.00217
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type Dependent Effect of Surface-Patterned Microdot Arrays on Neuronal Growth

Abstract: Surface micropatterns have been widely used as chemical cues to control the microenvironment of cultured neurons, particularly for neurobiological assays and neurochip designs. However, the cell-type dependency on the interactions between neurons and underlying micropatterns has been rarely investigated despite the inherent differences in the morphology of neuronal types. In this study, we used surface-printed microdot arrays to investigate the effect of the same micropatterns on the growth of mouse spinal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…In our case, neurite alignment along 30°, 90° and 150° radial angles was only obvious in the first two bins. Although others found that neurite growth pattern depends on the cell type37383940 in our study, a similar type of neurite growth was present in all three main subtypes of the DRG neurons, both neonatal and adult.…”
Section: Discussionsupporting
confidence: 49%
“…In our case, neurite alignment along 30°, 90° and 150° radial angles was only obvious in the first two bins. Although others found that neurite growth pattern depends on the cell type37383940 in our study, a similar type of neurite growth was present in all three main subtypes of the DRG neurons, both neonatal and adult.…”
Section: Discussionsupporting
confidence: 49%
“…An alternative method for studying single neurons in isolation is to use very-low-density cultures, which have been described in detail elsewhere (e.g., Goslin et al, 1998;Ventimiglia and Lindsay, 1998;Fath et al, 2009); I will not be discussing this approach here. I will also not be discussing the use of similar cultures to study neurite growth on patterned substrates, which is of interest to the design of brain-machine interfaces (e.g., Jang et al, 2016;Gautam et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The adaption of lithographic techniques to manipulate surface chemistry has paved the way for patterning 2D neural structures in vitro (Kleinfeld et al., 1988). Patterning of surface coatings with microcontact-printing has been utilized to create simple neural circuits (Jang et al., 2016, Jungblut et al., 2009, Marconi et al., 2012). However, both adhesive and repellant surface coatings, especially finer features (<10 μm), are unstable in culture, often degrading within one week (Wheeler and Brewer, 2010).…”
Section: Cns-on-chipmentioning
confidence: 99%